2015
DOI: 10.1007/s10495-015-1132-2
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin induces apoptosis preferentially via a Bim-mediated intrinsic pathway in hepatocarcinoma cells

Abstract: This report is designed to dissect the detail molecular mechanism by which dihydroartemisinin (DHA), a derivative of artemisinin, induces apoptosis in human hepatocellular carcinoma (HCC) cells. DHA induced a loss of the mitochondrial transmemberane potential (ΔΨm), release of cytochrome c, activation of caspases, and externalization of phosphatidylserine indicative of apoptosis induction. Compared with the modest inhibitory effects of silencing Bax, silencing Bak largely prevented DHA-induced ΔΨm collapse and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 63 publications
(143 reference statements)
3
54
0
Order By: Relevance
“…In parallel, DHA induced the expression of several autophagy‐related genes, including ATG12, BNIP3, and ULK1, and lowered the expression of mTOR, which normally represses autophagy. These data are in agreement with the reported ability of DHA to induce both apoptosis and autophagy in cancer cells. More than that, our study unravels a novel pathway through which DHA elicits its toxic effect.…”
Section: Discussionsupporting
confidence: 93%
“…In parallel, DHA induced the expression of several autophagy‐related genes, including ATG12, BNIP3, and ULK1, and lowered the expression of mTOR, which normally represses autophagy. These data are in agreement with the reported ability of DHA to induce both apoptosis and autophagy in cancer cells. More than that, our study unravels a novel pathway through which DHA elicits its toxic effect.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is unclear whether the normal p53 and retinoblastoma genes play a role in ARS-induced ROS-independent apoptosis pathway in HepG2 cells. Although drug sensitivity may correlate to the status of p53 [38], the same proapoptotic drug can induce apoptosis via p53-dependent and/or p53-independent pathways [21,39,40]. In addition, differences in the expression of drug metabolizing enzymes among these cell lines may also contribute to their different ARS response [41].…”
Section: Discussionmentioning
confidence: 99%
“…To verify whether HepG2 cells are resistant to ROS, we assessed the role of ROS in DHA-induced apoptosis in this cell line, and found that DHA induced a ROS-dependent apoptosis [40], indicating the controversial regulation mechanisms by which ARTs induce apoptosis in this cell line, and this discrepancy may be due to the different metabolic products from iron-ARS/DHA reactions. Moreover, we found that in other two HCC cell lines (Huh-7 and Hep3B), even though ARS induced a lower rate of ROS generation (data not shown), ARS induced a ROS-dependent apoptosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Artemisinin is frequently reported to induce apoptosis by the intrinsic mitochondrial pathway, mediated by caspase 3/9 activation and the release of cytochrome C following the permeabilization of the mitochondrial membrane . This form of artemisinin‐induced cell death can be affected by the manipulation of antiapoptotic proteins such as Bcl‐2, as well as proapoptotic factors such as Bid and Bak . Outside of the intrinsic pathway, the extrinsic/death receptor driven pathway has also been implicated in the action of artemisinin .…”
Section: Artemisinin‐induced Cell Death and Related Mechanismsmentioning
confidence: 99%